2007
DOI: 10.1002/masy.200750606
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Copolymer Bottle‐Brushes

Abstract: Summary:The structure of bottle-brush polymers with a rigid backbone and flexible side chains is studied in three dimensions, varying the grafting density, the side chain length, and the solvent quality. Some preliminary results of theoretical scaling considerations for one-component bottle-brush polymers in a good solvent are compared with Monte Carlo simulations of a simple lattice model. For the simulations a variant of the pruned-enriched Rosenbluth method (PERM) allowing for simultaneous growth of all sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Assuming the solvent is a theta‐solvent, side chains are only weakly stretched relative to free polymers in solution. This is a smaller exponent than what is predicted through scaling theories but consistent with simulations, which have found that the side chains are approximately Gaussian chains . The bottlebrush backbone is more extended than the side chains but retains significant conformational flexibility (a fully extended chain would have an end‐to‐end distance that scales linearly with N BB ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Assuming the solvent is a theta‐solvent, side chains are only weakly stretched relative to free polymers in solution. This is a smaller exponent than what is predicted through scaling theories but consistent with simulations, which have found that the side chains are approximately Gaussian chains . The bottlebrush backbone is more extended than the side chains but retains significant conformational flexibility (a fully extended chain would have an end‐to‐end distance that scales linearly with N BB ).…”
Section: Discussionsupporting
confidence: 77%
“…In general, studies have found that the side chains are only weakly stretched while the backbone is strongly elongated. Scaling theories predict that the side chain end‐to‐end distance scales with N 3/4 and N 2/3 in good and theta solvents, respectively, compared with N 3/5 and N 1/2 for free chains . Simulations predict weaker stretching of the side chains in a good solvent, with an end‐to‐end distance that scales with N 1/2 …”
Section: Introductionmentioning
confidence: 97%
“…On one hand, the first approach indicated that both PIB and PS arms were mainly surrounded by arms of the same chemical nature, as would be expected for a Janus organization as depicted on Both sets of experiments could however be reconciled by considering a patchy organization (Figure 6b) where the PIB and PS arms were essentially segregated, in agreement with the 1 H transverse relaxation results, but not perfectly, in agreement with the NOESY experiments. Such an incomplete phase segregation has actually been predicted by simulations 38 performed on covalent bottle-brush polymers bearing two incompatible arms. Its existence could be explained by the fact that even if phase segregation is favored at short length scales, creating alternating domains of phase segregated arms by allowing a few contacts between the two types of arms is entropically very favorable and enthalpically not too demanding, especially if the arms are not strongly incompatible.…”
Section: Interpretation Of the Solution-state Nmr Experimentssupporting
confidence: 54%
“…Recently there has been a great experimental (see e. g. [1,2,3,4,5,6,7]) and theoretical [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] interest in the conformation of so-called bottle-brush polymers. Such polymers consist of a long (flexible) main chain, at which many flexible (shorter) side chains are densely grafted, such that an overall shape of a worm-like cylindrical brush results [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%